Effect of a hydrogymnastics program on the serum levels of high-sensitivity C-reactive protein amongst elderly women - Hall Lopez, Javier Arturo (2014)
The aim of this study was to evaluate the effect of a hydrogymnastics training program on highsensitivity C-reactive protein in elderly women. The subjects were randomly divided into the experimental group who participates in the hydrogymnastics training program and the control group who was not involved in the training and remained sedentary. The serum levels of highsensitivity C-reactive protein were determined by immunoturbidimetry using C-reactive protein (CRP), the training protocol consisted of hydrogymnastics sessions 5 times per week during 12 weeks of intervention, executed in a pool of 1.3 meters divided into three phases: a 10-minute warm-up, 30 minutes of aerobic exercise at 50% - 60% of maximum heart rate (monitored by heart rate monitor) and a 10-minute cool down. As a statistical method to compare the results between groups of variables pre and post training, the analysis of variance (ANOVA) mixed 2 × 2 (group × measurement) test was done using SPSS version 17. The founds showed significant changes in the level of high-sensitivity C-reactive protein, and a greater percentage decrease of hs-CRP (Δ%= −37%, p = 0.001) in the experimental group in relation to the control group.